Glutathione S‐transferase theta genotypes and environmental exposures in the risk of canine transitional cell carcinoma. (22nd April 2019) - Luethcke, Katherine R.; Ekena, Joanne; Chun, Ruthanne; Trepanier, Lauren A.
Abstract: Introduction: Transitional cell carcinoma (TCC) in humans is associated with environmental exposures and variants in glutathione S‐transferase (GST) genes. Scottish Terriers have a high breed risk for TCC, but the relationship between genetic and environmental risk in dogs is not fully understood. Hypotheses: Scottish Terriers have a higher frequency of GST‐theta variants compared to lower risk breeds. Dogs with TCC of any breed have a higher frequency of GST‐theta variants along with higher environmental exposures, compared to controls. Animals: One hundred and five Scottish Terriers and 68 controls from lower risk breeds; 69 dogs of various breeds with TCC, and 72 breed‐ and sex‐matched unaffected geriatric dogs. Methods: In this prospective case‐control study, dogs were genotyped for 3 canine GST‐theta variants: GSTT1 I2+28 G>A, a GSTT1 3′UTR haplotype, and GSTT5 Asp129_Gln130del. Owners of dogs with TCC and unaffected geriatric controls completed a household environmental questionnaire. Results: The GSTT1 3′UTR haplotype and GSTT5 Asp129_Gln130del variants were significantly underrepresented in Scottish Terriers (minor allele frequency [MAF] = 0.000 for both), compared to dogs from lower risk breeds (MAF = 0.108 and 0.100; P ≤ .0002). Dogs with TCC did not differ from unaffected geriatric controls across the 3 investigated loci. Transitional cell carcinoma was associated with household insecticide use (odds ratio [OR] = 4.28, 95% confidence interval [CI] = 1.44‐12.33, P = .02), and was negatively associated with proximity to a farm (OR = 0.49, 95% CI = 0.25‐0.99, P = .04). Conclusions and Clinical Importance: Low‐activity GST‐theta loci are unlikely contributors to TCC risk in dogs. Increased risk is associated with household insecticide use, and possibly with less rural households.